Determinants of Investment Interest in the Islamic Capital Market among Generation Z in North Bungku Regency, Indonesia - Arnila Saputri; Evan Stiawan; Kustin Hartini (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the influence of investment motivation, investment knowledge, technological advancement, and investment risk on investment interest in the Islamic capital market among Generation Z in North Bungku Regency, Indonesia. This study used a quantitative approach with a survey method with a sample of 100 respondents selected through purposive sampling. Data were collected through a Likert scale questionnaire (1–10) distributed via Google Forms and analyzed using multiple linear regression. The results show that investment knowledge and investment risk have a positive and significant influence on investment interest, while investment motivation and technological advancement do not have a significant partial effect. Simultaneously, all variables significantly influence investment interest. These findings indicate that rational factors, such as knowledge and risk awareness, play a more dominant role than motivational and technological factors in shaping investment interest among Generation Z. This study implies the importance of improving financial literacy and risk understanding through structured educational programs to increase participation in the Islamic capital market. Future research is recommended to include additional variables such as religiosity and digital financial literacy, as well as a broader and more diverse sample.